The Kill order - Dashner, James, 1972- (New York : Delacorte Press, 2012)
"Mark struggles to make sense of his new, post-disaster world in this prequel to The Maze Runner"--
Prequel to: The maze runner.
Keywords: Survival -- Fiction; Virus diseases -- Fiction; Natural disasters -- Fiction; Science fiction